Measuring the proportion of time spent on work activities of clinical pharmacists using work sampling technique at a public hospital in Malaysia - Kian K. Kong; Siew C. Ong; Guat S. Ooi; Mohamed A. Hassali (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Background: The clinical pharmacy service to the ward was established in 2005 in Malaysia, as the number of pharmacists working in the public service sector began to grow. Yet, there has been little local research done on reporting the range of work activities of clinical pharmacists and the amount of time that they spent on their work activities. Objective: This study aimed to identify the range of work activities of clinical pharmacists by observation and to estimate the proportion of time spent on different work activities by using the work sampling technique. Methods: The time spent by clinical pharmacists on various activities was measured using the work sampling technique over 30 working days. The work activities of clinical pharmacists were pre-identified and customized into an activity checklist. Two observers were placed at the study site and took turns recording the activities performed by the clinical pharmacists by following a randomly generated observation schedule. Results: 1,455 observations were made on five clinical pharmacists with a total of 3493 events recorded. Overall, clinical pharmacists spent 78.8% (n=2751) of their time providing clinical services whereas 12.3% (n=433) of their time was spent on non-clinical activities. They were found to be idle from work for 8.9% of the time. There was no difference in bed occupancy rate in the study site regardless of the presence of the observer (p=0.384). Clinical pharmacists were found to report a higher average daily cumulative work unit of 9.8 (SD=4.3) when under observation compared to an average daily cumulative work unit of 6.5 (SD=4.6) when no observer was present (p=0.005). Conclusions: The results revealed that clinical pharmacists spent a significant amount of time on non-clinical work. Their responsibilities with non-clinical work should be properly taken care of so they can allocate more time to providing patient care.